动力包系统及动力包系统优化方法 (2018)
本发明公开了种动力包系统及动力包系统优化方法，涉及电站装备的变频应用技术领域，通过对于系统最优效率的追踪控制，从而可有效避免系统控制过程出现诸如大马拉小车等能量的浪费，即能够以最小的功率消耗，实现系统内各设备间的最优运行匹配，可实现在传统变频控制的基础上再节能3％～8％，进而能够在降低能耗的同时大大提升电厂的经济效益；同时，本申请中的技术方案中基于全集成优化控制策略的动力包系统还有利于电站装备的集成化、智能化升级，进而有助于整个产业链的升级改造。 The invention discloses a power pack system and a power pack system optimization method and relates to the technical field of frequency conversion applications of power station equipment. Through tracking and control of an optical efficiency of the system, energy waste phenomena such as driving of a trolley by a large horsepower during system control can be effectively avoided, namely optical operation matching between every two devices in the system can be realized at minimum power consumption, energy can be saved by 3%-8% on the basis of traditional frequency conversion control, and thus economic benefits of a power plant can be increased greatly along with energy consumption reduction; and meanwhile, the power pack system based on a full-integration optimization control strategy in th